Association of clinical and laboratory variables with risk of venous thromboembolism in high-grade serous ovarian cancer - Peippo, Maija H.; Perkonoja, Katariina; Isoviita, Veli-Matti; Hynninen, Johanna; Lassila, Riitta; Carpén, Olli (Wiley-Blackwell, 2025)
Objectives: This study aimed to assess the incidence and time course of venous thromboembolism and to survey clinical and laboratory features predicting the risk for these complications in patients with high-grade serous ovarian cancer.
Methods: Patients with high-grade serous ovarian cancer treated in a prospective ovarian cancer study at the Turku University Hospital between 2009 and 2020 were retrospectively analyzed for the incidence of venous thromboembolism. This diagnosis was based on the International Classification of Diseases, 10th Revision Coding, and confirmed from hospital electronic health records. Analyses combined multiple variables including treatment strategies and laboratory variables.
Results: Among the 146 patients with high-grade serous ovarian cancer, 24 (16.4%) had a confirmed venous thromboembolism. In 5 patients (3.4%), venous thromboembolism preceded the cancer diagnosis. The median time from cancer diagnosis to the venous thromboembolism event was 12.8 months. Patients with venous thromboembolism had shorter median survival (30.6 versus 41.6 months, p = .014), but age, disease stage at diagnosis, and co-morbidities were similar. In a multivariable analysis, short platinum-free interval (p < .005) and increased leukocyte (p = .004) and neutrophil (p = .013) counts both indicated an increased probability of venous thromboembolism event. Conversely, longer carbohydrate antigen 125 doubling time (p = .036), along with higher hemoglobin (p < .0001) and albumin levels (p = .015), were linked to a reduced risk of venous thromboembolism.
Conclusions: The combination of these findings in high-grade serous ovarian cancer patients could be incorporated into their venous thromboembolism risk stratification. Given the reduced overall survival in patients with venous thromboembolism, future studies should prioritize proactively targeted thromboprophylaxis.